The Implication of Godfatherism in the Appointments of Heads of LGC and Democratic Consolidation in Kogi State - Yusuf Adеjo Thomas; Okеmе Ukwumonu Patrick; Bеnjamin Jacob Aikoyе; Obi Suссеss Еsomсhi (International Journal of Qualitative Research, 2022)
Politicization has not brought about any significant development economically, socially, and politically. This research aims to assess the politicization of heads of LGC in Kogi State with reference to Dekina with emphasis on the recurrent issues. The systematic technique was used to draw 100 interview respondents and data obtained was analyzed descriptively via content analysis. Findings among others reveal that; the politicization of heads of LGC in Kogi State, in particular, is conceived as support towards an economic investment that must produce enormous dividend at all means. Inexperience, not-qualify, and visionless candidates are imposed by State governors (godfathers) for administrative and total control of the political system, has been manipulated to serve their whims and caprices to enhance their enrichment by looting government funds detriment of the governed. This negative practice of politicization (godfatherism) is a big termite eating deep into the political development of Kogi politics not until the electoral process produces a leader with a conscience with the love of the state at heart that will consider the welfare and wellbeing of the govern paramount, political stability and democratic development will not be achievable.